Comparison of Murder Criminal Law Based on Indonesia Criminal Law and Islandia Criminal Law - Ressi Nulastri (Journal of Law, Politic and Humanities, 2026)
Murder in Indonesia is still rampant, over the past four years there has been an increase in murder in Indonesia. In the context of comparative countries, an interesting country to compare is Islandia, because Islandia is the country with the lowest murder crime rate in the world. Therefore, this legal research aims to determine the substance of the crime of murder based on the Criminal Law in Indonesia and the Islandia Criminal Law and to determine the criminal policy towards the crime of murder in Indonesia in the future. This research is a normative legal research using a statute approach, a comparative approach, and a conceptual approach. The legal materials used in writing this law are primary, secondary, and tertiary legal materials. Primary legal materials are in the form of the Indonesian Criminal Code and the Islandia penal code while secondary legal materials are in the form of journals, theses, books, the internet, and tertiary legal materials are in the form of the Big Indonesian Dictionary, the Legal Dictionary, and scientific reports related to criminal law and the crime of murder. The legal material collection technique used is library research, and the legal material analysis technique uses the deductive method.